2016
DOI: 10.1111/his.12966
|View full text |Cite
|
Sign up to set email alerts
|

The application of next‐generation sequencing‐based molecular diagnostics in endometrial stromal sarcoma

Abstract: Our findings demonstrate good sensitivity and specificity of an NGS-based gene fusion assay in the detection of ESS fusion transcripts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Fusion genes in endometrial stromal sarcoma are amenable to detection through next generation sequencing, 26 and inherent to such testing methodologies is the identification of novel fusion products. To date, many of the gene fusion partners in both low-grade and high-grade endometrial stromal sarcoma remain to be identified; furthermore, the implicit biologic potential associated with these fusions remains to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion genes in endometrial stromal sarcoma are amenable to detection through next generation sequencing, 26 and inherent to such testing methodologies is the identification of novel fusion products. To date, many of the gene fusion partners in both low-grade and high-grade endometrial stromal sarcoma remain to be identified; furthermore, the implicit biologic potential associated with these fusions remains to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many of the gene fusion partners in both low-grade and high-grade endometrial stromal sarcoma remain to be identified; furthermore, the implicit biologic potential associated with these fusions remains to be fully characterized. Fusion genes in endometrial stromal sarcoma are amenable to detection through next generation sequencing, 26 and inherent to such testing methodologies is the identification of novel fusion products. Herein, we report two novel EPC1 genetic fusions arising from next generation sequencing in endometrial stromal sarcoma:…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data were collected. In addition, 14 untreated, molecularly well‐characterized [with fluorescence in‐situ hybridization (FISH) and/or next‐generation sequencing] endometrial stromal sarcomas (ESSs) were analysed, including nine low‐grade cases with JAZF1–SUZ12 fusion ( n = 6) or PHF1 rearrangement ( n = 3) and five high‐grade cases with YWHAE–NUTM2A/B fusion, as previously described . All of these ESSs were primary tumours, except for one metastatic lung tumour with JAZF1–SUZ12 fusion.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors suggest that JAZF1-SUZ12 fusion should become a specific tool when the diagnosis of ESS is unclear or difficult and it might be useful to differentiate LG-ESS from other smooth muscle uterine tumors. 26,27 Micci et al 28 have demonstrated the recombination between the PHF1 gene (PHD finger protein 1, from chromosomal band 6p21) and JAZF1 (JAZF1-PHF1). Further studies have shown the recombination between PHF1 and other genes (EPC1, MEAF6 or BRD8); these genes fusions encode proteins involved in transcriptional regulation 29 and their presumed oncogenic effects may be a lead part of the pathogenesis of ESS.…”
Section: Pathologymentioning
confidence: 99%